2021
DOI: 10.1097/ccm.0000000000004850
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes for Children Requiring Extracorporeal Membrane Oxygenation Therapy Following Hematopoietic Stem Cell Transplantation

Abstract: OBJECTIVES: The objective of this study was to provide an updated review of survival for pediatric hematopoietic stem cell transplantation patients requiring extracorporeal membrane oxygenation therapy as well as characterize the demographics, clinical variables, and complications associated with mortality. DESIGN: Retrospective database review of the Extracorporeal Life Support Organization Registry from 1990 to 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
3
12
0
2
Order By: Relevance
“…These reports have led to a renewal of interest and suggest improving outcomes for pediatric HCT patients supported with ECMO. This is also supported by recent reports that demonstrate improved survival of 26-50% for pediatric HCT patients supported with ECMO since 2010 (20,21).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…These reports have led to a renewal of interest and suggest improving outcomes for pediatric HCT patients supported with ECMO. This is also supported by recent reports that demonstrate improved survival of 26-50% for pediatric HCT patients supported with ECMO since 2010 (20,21).…”
Section: Introductionsupporting
confidence: 83%
“…Interval advancements in both peri-HCT support and critical care therapies have resulted in improved patient outcomes for pediatric HCT patients who require intensive care and critical care resources ( 13 , 14 , 32 ). This is supported by a recent report of the ELSO database by Olson, et al, which showed an improvement in survival to hospital discharge in pediatric HCT patient requiring ECMO from 3% between 1991 and 2009 to 26% between 2010 and 2019 ( 21 ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In patients post allogeneic HCT, the use of ECMO at our center was approximately two-fold higher than in patients with hematological malignancies (3.5%). Two of nine patients (22%) survived to discharge, which is within the range of data from the U.S. Pediatric Health Information System database and the Extracorporeal Life Support Organization (ELSO) registry (4,6,11). The fact that all seven patients surviving to discharge also are long-term survivors is notable considering the high rates of mortality reported within the first 90 days post ECMO treatment (12,13).…”
Section: Discussionsupporting
confidence: 52%
“…The fact that all seven patients surviving to discharge also are long-term survivors is notable considering the high rates of mortality reported within the first 90 days post ECMO treatment (12,13). While, despite signals for improved survival of ECMO in more recent years (10,11), status post allogeneic HCT, a diagnosis of leukemia, and granulocytopenia remain to be generally associated with higher odds of mortality relative to non-immunocompromised patients (4), clinical variables in our patients at initiation and during ECMO do not show any evidence for additional differences between patients post allogeneic HCT and those receiving chemotherapy for hematological malignancies. Indeed, although not reaching statistical significance, exploration of differences between survivors and non-survivors suggest a low vasoactive inotrope score (VIS) at initiation of ECMO, shorter duration of granulocytopenia, absence of emerging infections and bleeding complications, and absence of non-pulmonary organ failure during ECMO as being associated with survival.…”
Section: Discussionmentioning
confidence: 99%